Tuning the Lewis acidity of difluorido gold(iii) complexes: the synthesis of [AuClF2(SIMes)] and [AuF2(OTeF5)(SIMes)]. Issue 67 (2nd August 2018) - Ellwanger, Mathias A.; von Randow, Clara; Steinhauer, Simon; Zhou, Yunfei; Wiesner, Anja; Beckers, Helmut; Braun, Thomas; Riedel, Sebastian
Abstract : A route to [Au III ClF2 (SIMes)] and [Au III F2 (OTeF5 )(SIMes)] including structural characterization to tune the ligand arrangement and Lewis acidity of gold(iii ) centres was developed. Abstract : The synthesis and structural characterisation of the difluorido organo gold(iii ) complexes [AuClF2 (SIMes)] and [AuF2 (OTeF5 )(SIMes)] are presented. The substitution of a fluorido ligand in [AuF3 (SIMes)] by an OTeF5 group increases the Lewis acidity of the Au moiety. A scale for carbene affinities is presented, which correlates calculated and experimental values for the Lewis acidity of the metal centre in akin compounds.